Climate Change and Gender Action Plan of Mali - Ogwuike, Philomenaa; Dossou-Yovo Elliott Ronalda (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Mali is a landlocked, Sahelian country of West Africa. The Climate Change Vulnerability Index produced by ND-GAIN in 2016 ranked Mali as the 166th out of 181 most at climate change affected-risk countries in the world. It is the 9th most vulnerable country and the 43rd least ready country to address climate change effects. Mali is home to the inner delta of the Niger River that runs through nine countries in the region. The country is influenced by the Inter-Tropical Conversion Zone (ITCZ) which is, creating winds from Ocean and the winds from the Sahara region that are more dusty and warmer. The country is already experiencing the climate change impacts of droughts, flood, storms, strong winds, and increased temperature variability. These events have a devastating impact on crop yields, livestock production, and food security. Available facts show that Mali is among those countries extremely vulnerable to future climate vagaries, when climate change is expectedly going to increase local temperatures, the variability of rainfall, and the magnitude of extreme weather events. Gender relations are central in climate change discourse in Mali as men, women and youths play distinctly disproportionate roles in agriculture in Mali. Women specifically account for over 50% of agricultural labor, and are responsible for the majority of food production. Women, men and youth face varying levels of challenges in the agricultural sector, in accessing key production resource factors including land, water, and credit. Gender inequality defied prior progressive global, regional, and national commitments to protect and promote women’s rights. The Agriculture and Climate Change Gender Action Plan for Mali aims to address the gender dimensions of climate change in the agricultural sector. The plan has four key objectives, which include:- (i) increase women and youth's access to land, water, and credit. (ii) improve knowledge and skill of the various gender groups (women, men, and youths) in climate-smart agriculture with a determined effort to narrow down possible existing gender gaps among the groups. (iii) strengthen women's participation in decision-making and policy-making related to climate change. (iv) promote the use of gender-sensitive indicators to monitor and evaluate the plan's implementation. The plan is expected to have a number of benefits, including: • Increased food security and nutrition for women and their families. • Improved livelihoods for men, women, and youths. • Increased resilience to climate change. • Increased gender equality in the agricultural sector. The plan will be implemented by a number of government agencies, non-governmental organizations, and development partners. The plan is expected to be fully implemented by 2030.